The Role Of Facebook In Digital Promotion At Lanta Nice Beach Resort - Nuranissa, Dinda Widy; Kartini, Raden Asri; Adrial, Adrial (JMB : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the effectiveness of Facebook as a social media platform in enhancing tourist interest in Lanta Nice Beach Resort, Koh Lanta, Thailand. The research employs a quantitative approach with data collected through questionnaires distributed to tourists who have visited or interacted with the resort's social media account. The variables examined include the intensity of Facebook usage, the quality of visual content, user interaction, and its influence on visit interest. The findings reveal a significant positive relationship between Facebook-based digital promotion and the increase in tourist visits. Promotional strategies such as high-quality photo uploads, seasonal promotions, and interactive features contribute to building a positive perception of the resort's image. These findings indicate that social media, particularly Facebook, can serve as an effective promotional tool in the tourism industry if utilized strategically and consistently